Data supporting 'Biomarkers of postharvest resilience: unveiling the role of abscisic acid in table grapes during cold storage' - Alamar, M. Carmen; Falagán, Natalia; Terry, Leon A. (Cranfield University, 2023)
Physiological (colour, respiration rate, firmness), pathalogical (mould incidence) and biochemical (individual sugars, hormones, organic acids) data of table grapes during postharevst cold storage
Keywords: senescence'; 'ABA'; 'ethylene'; '1-methylcyclopropane'; 'table grapes'; 'postharvest'